2019
DOI: 10.2196/15787
|View full text |Cite
|
Sign up to set email alerts
|

A Chatbot Versus Physicians to Provide Information for Patients With Breast Cancer: Blind, Randomized Controlled Noninferiority Trial

Abstract: BackgroundThe data regarding the use of conversational agents in oncology are scarce.ObjectiveThe aim of this study was to verify whether an artificial conversational agent was able to provide answers to patients with breast cancer with a level of satisfaction similar to the answers given by a group of physicians.MethodsThis study is a blind, noninferiority randomized controlled trial that compared the information given by the chatbot, Vik, with that given by a multidisciplinary group of physicians to patients… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
103
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(106 citation statements)
references
References 7 publications
0
103
0
3
Order By: Relevance
“…Two groups of randomly assigned patients asked 12 predefined questions that were previously answered by a chatbot or a medical committee and received the response from either a chatbot or a physician. The chatbot group had higher success rates (69 vs. 64%) than the physician group, which showed noninferiority (P < 0.001) (17).…”
Section: Characteristics Of the Study Designmentioning
confidence: 87%
“…Two groups of randomly assigned patients asked 12 predefined questions that were previously answered by a chatbot or a medical committee and received the response from either a chatbot or a physician. The chatbot group had higher success rates (69 vs. 64%) than the physician group, which showed noninferiority (P < 0.001) (17).…”
Section: Characteristics Of the Study Designmentioning
confidence: 87%
“…In this phase III, non-inferiority, randomized, blind, controlled trial, the EORTC INFO25 scores from the chatbot were found to be non-inferior to the scores of the group of physicians [10]. As a consequence, the tools have the same limitation.…”
Section: Introductionmentioning
confidence: 79%
“…Commercial products using artificial intelligence to capture patient's symptoms and health concerns from emails to guide scheduling, and online tools that use chatbots to triage patient requests for appointments are already under development. 21,22 The interpretation of this study's results has limitations. First, we used email as a proxy for patient engagement, which might not be an appropriate assumption.…”
mentioning
confidence: 86%